Cleopatra (United States 20th Century Fox Film Productions, 1963)
Following Caesar's triumphant Battle of Pharsalia, the mighty warrior goes to Alexandria, where he and Queen Cleopatra begin an affair. She fuels his desire to become the sole ruler of the Roman Empire, an ambition that leads to his assassination. After his death, Rome is ruled by Octavius, Mark Antony and Lepidus. But Antony, who was Caesar's second-in-command, falls in love with Cleopatra and is torn between his duty to Rome and his passion for her.
Disc 1 (57 min.) -- disc 2 (60 min.) -- disc 3 (1 hr., 12 min.) -- disc 4 (1 hr., 2 min.)
VCD.
Screenplay by Joseph L. Mankiewicz, Ranald MacDougall and Sudney Buchman based upon histories by Plutarch, Suetonius, Apian, other ancient sources and "The life and times of Cleopatra" by C. M. Franzero ; produced by Walter Wanger ; directed by Joseph L. Mankiewicz.
Elizabeth Taylor, Richard Burton, Rex Harrison.
Keywords: Cleopatra -- Queen of Egypt -- d. 30 B.C. -- Drama; Queens -- Egypt; Egypt -- History -- 332-30 B.C.; Epics